GELIAT POLITIK ISLAM LOKAL DI INDONESIA TAHUN 1998-2021 (STUDI POLITIK ISLAM DAERAH KEDIRI, ACEH DAN SUMENEP) - Ratih Himamatul Azizah T (Asketik : Jurnal Agama dan Perubahan Sosial, 2021)
This article examines Islamic political governance in Indonesia. Islamic political revival began in thereform era. Reform era provides democratic space for national political parties and local politicalparties in exploring democracy in the regions. Islamic politics in the region has different forms incarrying it out and does not lose the side of locality because it is in accordance with the socio-culturalconditions of the local community. Islamic politics in kediri by adjusting the socio-cultural conditionthe people tidak kagetan so that the form of Islamic politics kediri is an tolerant. Politics Islamic insumenep etnic islam politics with the philosophy “bhuppa’, bhabu’, guru, rato” the from of leadershiprespect the kiai as a teacher and rules. Islamic politics in aceh with characteristics maintains Islamicpolitics in accordance with Allah provisions.